Traditional Games in Enhancing Development Children’s Gross Motoric: Literature review - Nurwiyanto, Anton Dwi; Kumaat, Noortje Anita; Wijaya, Fransisca Januarumi Mahaendra (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Many students learn to use digital media or smartphones, but after that they immediately play games using the smartphone. This is a problem in children’s daily and sustainable activities. This study aims to determine the kinds of traditional games that can improve children’s gross motoric development. This rerearch used types qualitative research with the literature study method or known as a literature review. The library selection technique is based on the keywords used, namely traditional games on gross motoric development of elementary school students . The literature obtained comes from google scholar in the form of national journals for the last 8 years. Literature review uses a synthetic matrix in the form of reference sources, types of samples, methods, interventions, and findings. The results of this study were that 9 articles were reviewed.